Design and optimization of sustainable passive treatment systems for phosphogypsum leachates in an orphan disposal site. (1st December 2020) - Millán-Becerro, Ricardo; Pérez-López, Rafael; Macías, Francisco; Cánovas, Carlos R.
Abstract: The optimization of the dispersed alkaline substrate (DAS) technology was investigated to achieve the treatment of highly acidic and polluted effluents from a phosphogypsum pile in an orphan site of SW Spain. This phosphogypsum disposal area is located on the Tinto river marsh soils, where it acts as a source of pollution for the estuarine environment, releasing high concentrations of metal(loid)s and radionuclides, which degrade the surrounding waters. The methodology consists of flowing the leachates through columns loaded with a combination of a fine-grained alkaline reagent scattered in a non-reactive matrix to raise the water pH while decreasing the solubility of dissolved contaminants. Seven columns were built, one for each of the alkaline reagent used: limestone, barium carbonate, biomass ash, fly ash, MgO, Mg(OH)2, and Ca(OH)2 . The Ca(OH)2 -DAS and MgO-DAS treatment systems showed the highest effectiveness, reaching near-total removal for PO4, F, Fe, Zn, Cu, Al, Cr, and U with initial reagent mass:treated volume ratios of 36.3 g/L and 7.57 g/L, respectively. Total As removal was only achieved in the Ca(OH)2 -DAS treatment. Phosphate precipitation was the main mechanism responsible for pollutants removal. Geochemical modeling using PHREEQC code and mineralogical evidence confirmed the precipitation of these minerals. This study forms the basis of an effective and environmentally sustainable treatment system for phosphogypsum leachates to reduce the impact of the fertilizer industry worldwide. Graphical abstract: Image 1 Highlights: Hazardous phosphogypsum leachates were treated by a passive treatment method. Disperse Alkaline substrate (DAS) treatment improved notably the water quality. The Ca(OH)2 and MgO-DAS reached a near total removal of PO4, F, Fe, Zn, Cu, Al and U. Phosphate minerals are the main scavengers of pollutants during the treatment. DAS technology is suitable to treat highly-pollutant phosphogypsum leachates.